2013
DOI: 10.5489/cuaj.444
|View full text |Cite
|
Sign up to set email alerts
|

Urinary PSA: a potential useful marker when serum PSA is between 2.5 ng/mL and 10 ng/mL

Abstract: Urinary PSA: a potential useful marker when serum PSA is between 2.5 ng/mL and 10 ng/mL ORIGINAL RESEARCH Abstract Introduction: Our objective was to evaluate the usefulness of urinary prostate specific antigen (PSA) in the differential diagnosis of benign prostatic hyperplasia (BPH) and prostate cancer. Methods:We undertook a prospective study and obtained informed consent from 170 men. They provided blood samples to measure serum PSA and 50 mL of firstvoided urine to measure urinary PSA. Seventy-seven men we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 18 publications
4
42
0
Order By: Relevance
“…(19)(20)(21)(22)(23)(24) However, concomitant decrease in urinary PSA level occurs that is its level decreases in cancerous conditions than in benign conditions (though the actual urinary level remains higher than serum PSA).This has been potentially explained by an altered drainage of prostate secretions in prostatic urethra which leads to decreased excretion of total PSA and thereby increase in serum total PSA. (25) Our findings regarding levels of urinary fPSA in prostatic malignancies compared to benign states of prostate corroborates with Bolduc S et al (2007). The difference in mean ranks of fPSA of cases (16.05) and controls (30.88) in the present study shows high statistical significance (U=43.50, p<0.001) ( Table: 1). MMP expression in prostate cancer was first described in 1991 by in situ hybridisation methods.…”
Section: Discussionsupporting
confidence: 77%
“…(19)(20)(21)(22)(23)(24) However, concomitant decrease in urinary PSA level occurs that is its level decreases in cancerous conditions than in benign conditions (though the actual urinary level remains higher than serum PSA).This has been potentially explained by an altered drainage of prostate secretions in prostatic urethra which leads to decreased excretion of total PSA and thereby increase in serum total PSA. (25) Our findings regarding levels of urinary fPSA in prostatic malignancies compared to benign states of prostate corroborates with Bolduc S et al (2007). The difference in mean ranks of fPSA of cases (16.05) and controls (30.88) in the present study shows high statistical significance (U=43.50, p<0.001) ( Table: 1). MMP expression in prostate cancer was first described in 1991 by in situ hybridisation methods.…”
Section: Discussionsupporting
confidence: 77%
“…In a group of patients with PSA of 2.5-10.0 ng/mL, Bolduc et al 73 found a significant difference in mean uPSA in BPH (123.2 ng/mL) and PCa (52.6 ng/mL). With the uPSA threshold > 150 ng/mL, the sensitivity of the test was 92.5%.…”
Section: Determination Of Psa In the Urine In The Diagnosis Of Bphmentioning
confidence: 95%
“…Efforts to adapt urine as a source of biomarkers for prostate cancer have been made using various approaches. For instance, DNA markers such as GSTP1 hypermethylation (55), RNA markers such as PCA3 (56), and protein markers such as ANXA3 (57), matrix metalloproteinases (58), and urinary versus serum PSA (59,60). In light of the clinical relevance of urine samples, we accessed EPS-urine for verification and potential future assay development of our candidate biomarkers.…”
Section: Discussionmentioning
confidence: 99%